Education in Laboratory Management for Pathology Residents - Hale, Joseph H.; Coles, F. Bruce (American journal of clinical pathology, 1987)
In addition to clinical expertise, pathologists are required to have a background in areas of management, administration, and computer operations. During their training, it is imperative that pathology residents have exposure to the subject of modern laboratory management. The authors feel that a rotation in administration is not adequate to give the necessary training but that a formal program is needed to achieve this goal. They have developed a course in laboratory management that uses the available resources of their own department and hospital to meet these needs.